Genetic and metabolic mechanisms underlying webbed feet pigmentation in geese: Insights from histological, transcriptomic, and metabolomic analyses - Yi Liu; Kaiqi Weng; Guangquan Li; Huiying Wang; Yu Tan; Daqian He (Poultry Science)
This study systematically investigated the genetic and metabolic mechanisms underlying pigmentation in goose webbed feet by integrating histological, transcriptomic, and metabolomic analyses. Histological examinations revealed significant differences in melanin deposition among webbed feet of varying colors. Dark black webbed feet exhibited the highest melanin content, light black webbed feet showed moderate levels, and colorless webbed feet lacked detectable melanin. Transcriptomic analysis identified substantial variations in the expression levels of key genes involved in melanin biosynthesis, including TYRP1, PMEL, DCT, TYR, OCA2, MC1R, RAB38, WNT16, CAMK2A, and MLANA, between pigmented and colorless webbed feet. Notably, the OCA2 gene exhibited significantly higher expression in dark black webbed feet compared to light black webbed feet, underscoring its pivotal role in regulating pigmentation intensity. Enrichment analysis emphasized the importance of pathways related to tyrosine metabolism, melanin production, and amino acid biosynthesis in determining pigmentation differences. Metabolomic profiling supported these findings, revealing that L-tyrosine and 5,6-dihydroxyindole-2-carboxylic acid are critical metabolites in the melanin biosynthesis pathway. Specifically, elevated levels of L-tyrosine were detected in colorless webbed feet, likely due to inhibited melanin synthesis, whereas 5,6-dihydroxyindole-2-carboxylic acid levels were highest in dark black webbed feet, reflecting active melanin production. Correlation analysis between transcriptomic and metabolomic data further validated the central role of tyrosine metabolism and melanin biosynthesis pathways in pigmentation. In conclusion, this study employed multi-omics approaches to elucidate the critical role of the OCA2-centered genetic-metabolic regulatory network in melanin deposition of goose webbed feet, providing important insights into the molecular mechanisms of avian pigmentation and valuable references for poultry breeding.